REVITALISASI TAMAN BERMAIN DALAM MENGEMBANGKAN POTENSI DESA KARANGDIYENG - Galuh Salma Sabriana Eka; Jovanca Esperdion Wakum; Ari Ade Prasetyo; Nafaricha Putri Qurbawati; Febryanti Ina Gita; Mahendra Dwi Pramana; Mohammad Fadhil Fahreza; Johanes Alfredo Hutajulu (Prosiding Patriot Mengabdi, 2023)
REVITALISASI TAMAN BERMAIN DALAM MENGEMBANGKAN POTENSI DESA KARANGDIYENG